A Cable-Driven Exoskeleton With Personalized Assistance Improves the Gait Metrics of People in Subacute Stroke - Bin Zhong; Mei Shen; Haowen Liu; Yijun Zhao; Qiuyang Qian; Wei Wang; Haoyong Yu; Mingming Zhang (IEEE, 2023)
Most stroke survivors have mobility deficits and show a pathological gait pattern. Seeking to enhance the gait performance among this population, we have developed a hybrid cable-driven lower limb exoskeleton (called SEAExo). This study aimed to determine the effects of SEAExo with personalized assistance on immediate changes in gait performance of people after stroke. Gait metrics (i.e., the foot contact angle, knee flexion peak, temporal gait symmetry indices) and muscle activities were the primary outcomes to evaluate the assistive performance. Seven subacute stroke survivors participated and completed the experiment with three comparison sessions, i.e., walking without SEAExo (served as baseline) and without/with personalized assistance, at their preferred walking speeds. Compared to the baseline, we observed increases in the foot contact angle and knee flexion peak by 70.1% ( ${p} < 0.05$ ) and 60.0% ( ${p} < 0.05$ ) with personalized assistance. Personalized assistance contributed to the improvements in temporal gait symmetry of more impaired participants ( ${p} < 0.05$ ), and it led to a 22.8% and 51.3% ( ${p} < 0.05$ ) reduction in the muscle activities of ankle flexor muscles. These results demonstrate that SEAExo with personalized assistance has the potential to enhance post-stroke gait rehabilitation in real-world clinical settings.